The legal definition of terrorism and the enemy's criminal law: a critical analysis in the light of fundamental rights - Rosa, Gerson Faustino (2023)
This work aims to analyze the legal definition of terrorism presented by Law nº 13.260/2016 in the light of fundamental rights and guarantees. The research begins with a brief exhibition of the historical-world origin of terrorism, analysis of the express command inserted in the constitutional text of criminalization and heinousness and the study of the expression "acts of terrorism" contained in the National Security Act. Describes the historical-social context of the elaboration of the Brazilian anti-terrorism law and the difficulty of the ordinary legislator in creating a penal type of terrorism that respects the principles of legality and specificity, when entering in the incriminating standard vague expressions and of undetermined reach and still seeks to describe and analyze what legal assets intended to protect with the type in question. Presents the characteristics of the theory elaborated by Günther Jakobs who believes in the existence of two penal rights, one applied to the citizen and the other applied to the enemy and what are the implications and reflections of his theory in the elaboration of Law nº 13.260/2016, considered a law of Instrumental prevention that violates various constitutional precepts present in our legal order.